Semaglutide and the Risk of Non-Arteritic Anterior Ischaemic Optic Neuropathy: A Systematic Review and Meta-Analysis - Jovita Jutamulia; Elfira Sutanto (Open Access Indonesian Journal of Medical Reviews, 2026)
Semaglutide, a glucagon-like peptide-1 receptor agonist (GLP-1 RA), has emerged as an effective treatment for type 2 diabetes mellitus and obesity management. However, recent pharmacovigilance and observational studies have raised concerns regarding a potential association between semaglutide use and non-arteritic anterior ischaemic optic neuropathy (NAION), a serious form of optic neuropathy causing sudden vision loss. We conducted a systematic review and meta-analysis of observational studies examining the association between semaglutide exposure and NAION risk. We searched PubMed, Embase, and Google Scholar without date restrictions, with the final search completed on 31 March 2026. Study selection was based on predefined inclusion criteria, and quality was assessed using the Newcastle-Ottawa Scale (NOS). A random-effects model was used to estimate pooled hazard ratios (HR) with 95% confidence intervals (CI). Heterogeneity was quantified using the I² statistic. Publication bias was examined using funnel plots and Egger’s regression test. Six observational studies comprising 699,141 participants were included in the meta-analysis. Overall, semaglutide was associated with a significantly increased risk of NAION (pooled HR 1.802; 95% CI 1.221–2.658; p = 0.003). Substantial heterogeneity was observed (I² = 72.8%, Q = 18.37, p = 0.003). Subgroup analyses revealed that the positive association was driven by four prospective cohort studies reporting elevated NAION risk (HR = 2.402; 95% CI 1.662–3.468), whereas two retrospective studies reported null associations (HR = 0.98; 95% CI 0.60–1.60). Sensitivity analyses demonstrated robustness of the primary finding. In conclusion, this meta-analysis provides evidence of a potential increased risk of NAION associated with semaglutide use in observational studies, particularly among individuals with type 2 diabetes and obesity. Clinical awareness of this signal is warranted, and further prospective investigation is recommended.